(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The objective of the writing is to analyze the causes and consequences of the stockout of affordable national red beans in Nicaragua’s domestic market. During the making of document were observed elements that incorporate the phenomenon, in order to reason and retake holistic thematic and subsequently generate proposals of viable causes and consequences that could explain the aforementioned red bean shortage in national market. Likewise, were considered specific times (price), facilitators of comparative and correlational analysis of the event in regard to other periods. Thence arises as a result, the warning of the preponderant role of producers, merchants and government as agents that influence the evolutionary development of the discoursed topic. However, it is essential to mention that its influence on the economy has a direct and proportional impact, affecting predominantly the plaintiff of good, in this case "red bean". DOI: http://dx.doi.org/10.5377/reice.v2i4.1728 REICE Vol. 2, No. 4, julio-diciembre 2014: 96-109